2006
DOI: 10.1007/s00198-006-0077-2
|View full text |Cite
|
Sign up to set email alerts
|

ALDH2 polymorphisms and bone mineral density in an elderly Japanese population

Abstract: The present results suggest that active prophylactic interventions such as dietary, exercise, and pharmacological therapies should be offered to non-carriers of the Glu allele (Lys/Lys).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 43 publications
2
29
1
1
Order By: Relevance
“…Contrary to the results presented here, it has been reported that GSTM1 and GSTT1 gene deletion genotypes do not significantly affect susceptibility to osteoporosis in Japanese osteoporotic patients assessed using ultrasound bone tissue measurement [24]. According to published data, the genetic diversity in the Japanese population shows slightly higher GSTM1*0 genotype (55.8%) and significantly higher GSTT1*0 genotype (40.0%) frequencies than in the Slovenian population (49.0% and 21.3%, respectively).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the results presented here, it has been reported that GSTM1 and GSTT1 gene deletion genotypes do not significantly affect susceptibility to osteoporosis in Japanese osteoporotic patients assessed using ultrasound bone tissue measurement [24]. According to published data, the genetic diversity in the Japanese population shows slightly higher GSTM1*0 genotype (55.8%) and significantly higher GSTT1*0 genotype (40.0%) frequencies than in the Slovenian population (49.0% and 21.3%, respectively).…”
Section: Discussioncontrasting
confidence: 99%
“…While there are data on their potentiation of risk of cytogenetic damage in many diseases, only one osteoporosis-association study on deletion polymorphisms of GSTT1 and GSTM1 genes has been reported; it showed no significant association with bone density values in an elderly Japanese population [24].…”
Section: Introductionmentioning
confidence: 97%
“…In humans, however, the suppression of ALDH2 activity by ALDH2*2 causes various disorders, presumably because of increased oxidative stress. For instance, ALDH2 deficiency was found to contribute to the risk of complication with diabetes mellitus, hypertension, myocardial infarction, osteoporosis, and cancer (Suzuki et al, 1996;Amamoto et al, 2002;Takagi et al, 2002;Yokoyama and Omori, 2003;Yamaguchi et al, 2006). Therefore, we expected the development of model animals closer to humans by introducing the ALDH2*2 gene.…”
Section: Discussionmentioning
confidence: 99%
“…ALDH2*2 and osteoporosis: Osteoporosis is characterized by a decrease in bone mineral density, bone mass, and bone strength, which ultimately leads to an increased risk of fracture [59]. In a genetic screen of known osteoporosis related genes in 403 elderly Japanese, ALDH2*2 was the only mutation strongly associated with the risk of osteoporosis [60]. This association was especially prevalent in ALDH2*2/2 homozygotes and in women.…”
Section: Diseases Associated With the Inheritance Of Aldh2*2mentioning
confidence: 99%